Philosophy of State: The Social Contract and the Separation of Powers according to John Locke - Nur Rohim Yunus (ADALAH, 2019)
The social contract is a reasoned agreement regarding the authority of governmental authorities and the extent of social freedom. To further improve justice and achieve high morals, a social contract based on the free will of all was established. Yet, according to John Locke, the social compact is a motivating factor in the shape of a desire to avoid interference, in which the individual surrenders no important natural rights to the society, but simply the right to implement natural law. Individuals' submitted rights are not granted to individuals or groups, but rather to the entire community. So, the nature of government is limited power, political authority is borrowed, and power is constrained by the government's own objectives, notably the protection of fundamental human rights. Moreover, John Locke encouraged the separation of powers in a nation, so that it does not rely on a single power.